Solubility Characteristics and Slow-Release Mechanism of Nitrogen from Organic-Inorganic Compound Coated Urea - Hongtao Zou; Yao Ling; Xiuli Dang; Na Yu; YuLing Zhang; YuLong Zhang; Jianghui Dong (International Journal of Photoenergy)
A soil incubation method was used to investigate the solubility characteristics and slow-release mechanism of organic-inorganic compound coated urea at temperature of 10, 20, and 30°C. The membrane microstructure with and without incubation was tested via scanning electron microscopy (SEM). Slow release of nitrogen (N) from different inorganic minerals was analysed by the activation energy from the nutrient solubility system. The rate of nitrogen solubility increased with temperature increasing. The first-order reaction kinetic equation described the solubility process of coated urea. The rate constant k also increased with temperature increasing. Moreover, the SEM images showed that the microstructure of the coating layer changed into a flocculent structure and the number of tiny pores and holes on the membrane surface increased significantly with temperature increasing, which increased N solubility rate. The Arrhenius equation indicated that activation energy was closely related to k during the solubility process; the activation energy was reduced with k rising, which resulted in N solubility rate increasing. Overall, the N solubility rate of coated urea was affected by temperature.